Artemis Base Camp and Exploitation of Outer Space: Problems and The Needs of Legal Framework - Irawati Handayani; Annisa Juliana; Garry Gumelar (Padjadjaran Journal of International Law, 2023)
NASA introduced the Artemis Program in 2017, consisting of several missions, such as establishing a permanent outpost called Artemis Base Camp and exercising commercial and non-commercial exploitation on the Moon. For the program to be carried out properly, the United States established a series of bilateral agreements with other countries, namely the Artemis Accords. One of the functions of the Accords is as the supporting legal instrument for the implementation of the Artemis Program. However, its implementation raised several legal problems related to the legality of establishing Artemis Base Camp and violations of the basic principles of space law related to activities. This paper will specifically discuss the legal issues arising from using the Artemis Accords as one of the supporting legal bases for the two Artemis Program activities, according to space law. This article argues that Artemis Base Camp falls within the definition of a station explained in the Outer Space Treaty and the Moon Agreement. Then, the construction does not violate the principle of non-appropriation in Article II of the Outer Space Treaty because it does not fulfill the three main components of appropriation activities. Although establishing the Artemis Base Camp and exploiting lunar resources for non-commercial purposes is permitted, a basic legal framework still needs to be established to regulate permanent outposts and the exploitation of lunar resource activities. A specific legal framework is needed to avoid multiple interpretations leading to legal uncertainty.